Quantitative easing, portfolio rebalancing and credit growth: Micro evidence from Germany - Johannes Tischer (Deutsche Bundesbank, 2018)
This paper sheds light on the effect of quantitative easing (QE) on bank lending. Using data on German banks for 2014-2016, I show that QE encourages banks to rebalance from securities to loans. For identification, I use bond redemptions as exogenous variation in banks' need to rebalance their portfolio and hence their exposure to QE. I find that more exposed banks increase their loan growth during QE relative to other banks. The growth differential is larger when bond market yields decrease stronger than loan market yields and for banks with equity constraints. These results imply that QE can affect bank lending even if banks do not hold assets purchased under the QE program, by increasing incentives to invest in higher-yield assets.
Keywords: E51; E58; G11; G21; 330; quantitative easing; bank lending; proprietary trading; monetary transmission